A hairy-bodied tettigarctid (Hemiptera: Cicadoidea) from the latest Middle Jurassic of northeast China. Issue 3 (2nd July 2016) - Liu, Xiao-Hui; Li, Yi; Yao, Yun-Zhi; Ren, Dong
Abstract : Liu, X.H., Li, Y., Yao, Y.Z. & Ren, D., April 2016. A hairy-bodied tettigarctid (Hemiptera: Cicadoidea) from the latest Middle Jurassic of northeast China. Alcheringa 40, xxx–xxx. ISSN 0311-5518 Extant tettigarctids are also known as hairy cicadas because they are covered by long and abundant hairs. This character had not been reported in fossil species of Tettigarctidae because previous examples were poorly preserved or lacked long hairs. Hirtaprosbole erromera gen. et sp. nov. (Tettigarctidae) with a hairy body, from the latest Middle Jurassic Jiulongshan Formation of Daohugou, Inner Mongolia, China, is described here. This new species provides evidence that tettigarctids with long dense hairs had appeared by the latest Middle Jurassic and lived at high altitudes. Xiao-hui Liu [ liuxh8917@163.com ], Yi Li [ liy0124@sina.com ], Yun-zhi Yao*[Corresponding author: yaoyz100@gmail.com ] and Dong Ren [ rendong@mail.cnu.edu.cn ], College of Life Sciences, Capital Normal University, Xisanhuanbeilu 105 Haidian District, Beijing, PR China 100048.